2020
DOI: 10.1186/s12864-020-6473-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptomics reveals candidate carotenoid color genes in an East African cichlid fish

Abstract: Background Carotenoids contribute significantly to animal body coloration, including the spectacular color pattern diversity among fishes. Fish, as other animals, derive carotenoids from their diet. Following uptake, transport and metabolic conversion, carotenoids allocated to body coloration are deposited in the chromatophore cells of the integument. The genes involved in these processes are largely unknown. Using RNA-Sequencing, we tested for differential gene expression between carotenoid-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 118 publications
4
53
0
Order By: Relevance
“…In this case, Toews et al (2016) showed that the genomes of these bird species are highly differentiated at the locus that encodes the carotenoid degradation gene, BCO2. Similarly, a transcriptomic approach in an African cichlid fish, Tropheus duboisi, revealed greater expression of BCO2; and lower expression of carotenoid uptake gene SCARB1 was associated with white versus yellow skin (Ahi et al, 2020). Variation among H. rubra lineages in the functionality or expression of BCO2, carotenoid bioconversion enzymes, or any of the other carotenoid metabolism proteins could result in the observed differences in carotenoid content in this study.…”
Section: Crustacean Carotenoids and Genessupporting
confidence: 56%
“…In this case, Toews et al (2016) showed that the genomes of these bird species are highly differentiated at the locus that encodes the carotenoid degradation gene, BCO2. Similarly, a transcriptomic approach in an African cichlid fish, Tropheus duboisi, revealed greater expression of BCO2; and lower expression of carotenoid uptake gene SCARB1 was associated with white versus yellow skin (Ahi et al, 2020). Variation among H. rubra lineages in the functionality or expression of BCO2, carotenoid bioconversion enzymes, or any of the other carotenoid metabolism proteins could result in the observed differences in carotenoid content in this study.…”
Section: Crustacean Carotenoids and Genessupporting
confidence: 56%
“…The gene gch2 encoding a pivotal protein in the pteridine biosynthetic pathway and is required for xanthophore pigmentation in zebrafish 48 . Also hsd3b1 and ttc39b have been linked to lipid and carotenoid synthesis as well as carotenoid-based coloration differences in cichlids 47,[53][54][55] . Compared to the dark morph, xanthophores are numerous in the yellow morph and densely filled with xanthosomes as supported by light microscopy (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…4; Table 2). Those six pigmentation genes were hydroxy-delta-5-steroid dehydrogenase, 3 beta-and steroid delta-isomerase 1 (hsd3b1) 47 , pteridine biosynthesis enzyme GTP cyclohydrolase 2 (gch2) 48 , carotenoid droplets disperser perilipin 6 (plin6) 49 , melanophore-linage cell marker microphthalmia-associated transcription factor a (mitfa) [50][51][52] , tetratricopeptide repeat protein 39B (ttc39b) [53][54][55] and oncogenic transcription factor forkhead box Q1 (foxq1a) 56 .…”
Section: Three-dimensional Arrangement Of Chromatophores and Their Prmentioning
confidence: 99%
“…In recent years, carotenoids accumulation in bivalves was documented in Argopecten irradians [28], Hyriopsis cumingii [30] and Patinopecten yessoensis [30]. Previous studies have shown that the mechanisms of carotenoid accumulation in bivalves involved carotenoids absorption, transportation, deposition, and metabolic processing [3]. Several genes involved in carotenoid accumulation have been identi ed, for example, in our previous study, a scavenger receptor (SRB-like-3) gene shows a signi cantly correlation with the concentration of carotenoids in the tissues of noble scallops [18].…”
Section: Discussionmentioning
confidence: 99%
“…Carotenoids are ubiquitous in the natural environment, which synthesized by plants, some bacteria and fungi [1]. Animals must acquire carotenoids through their diet, and then modi ed carotenoids to self-speci c [2,3]. In recent years, the advance in sequencing methods has deepened our understanding of the genetics process of carotenoids in animals, for example, the genes and pathways involved in carotenoids absorption, transportation and metabolism [3].…”
Section: Introductionmentioning
confidence: 99%